Stability analysis of expansive soil slopes considering shear strength decay characteristics - Jinpeng LI; Lei WANG; Jun WANG; Yang CHEN; Yongfu XU (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
In order to address the problem that the dynamic decay of shear strength of expansive soil in the process of rainfall infiltration cannot be considered in the traditional slope stability analysis of expansive soil, indoor direct shear test was carried out to systematically study the influence of dry density and water content on the indicators of shear strength of expansive soil, viz., cohesion and internal friction angle. At the same time, the stability analysis of the expansive soil slope based on the strength reduction method was carried out with the shear strength testing results, and the change law of slope stability with the dynamic decay of shear strength was obtained. The results show that the increase of water content and the decrease of dry density will cause the decay of cohesion and internal friction angle of expansive soil, and the decay of cohesion is significant, while the decay of internal friction angle is less; the stability of expansive soil slope is mainly controlled by the water content of weathering layer, and with the increase of water content of expansive soil, the slope gradually evolves from stable state to unstable state, while the influence of dry density on the stability of expansive soil slope is relatively small.